Morphophysiological changes and reactive oxygen species metabolism in Corchorus olitorius L. under different abiotic stresses - Rahman Khussboo (De Gruyter, 2021)
Abiotic stress has become an alarming issue for plant survival due to the constant changes in the environment. Abiotic stresses such as drought, salt, waterlogging, and heavy metals largely influence plant growth and development that finally reduce crop productivity. The present study was carried out to investigate the responses of jute (Corchorus olitorius cv. O-9897) plant under different abiotic stresses. At 15th days after sowing plants were exposed to different abiotic stresses for various duration. Two doses of NaCl (200 and 400 mM) were applied to impose salt stress, while two doses of CdCl2 (2 and 4 mM) were applied for cadmium (Cd) stress. Waterlogging stress was applied for 5 and 15 days. Whereas drought stress was imposed on plants for 10 and 15 days. Leaf relative water content, SPAD value, plant height, above ground fresh and dry weight, leaf area, and stem diameter decreased upon exposure to salt, water deficit, Cd, and waterlogging stresses. These abiotic stresses resulted in oxidative damage which was evident by the increased levels of lipid peroxidation, H2O2, and electrolyte leakage (EL) together with altered antioxidant enzymes activities and glyoxalase system which are crucial for plants to fight against oxidative damage. Both duration of waterlogging and drought stress drastically affected plant morphophysiology, whereas C. olitorius could tolerate moderate level of salt (200 mM NaCl) and Cd (2 mM CdCl2). So the present study reveals that abiotic stresses cause substantial damages to the morphophysiology and oxidative stress tolerance of C. olitorius where the higher doses of NaCl and CdCl2 as well as the increased duration of waterlogging and drought resulted in more deleterious effect.